2018
DOI: 10.1002/ece3.3987
|View full text |Cite
|
Sign up to set email alerts
|

Difference in plasticity of resting metabolic rate – the proximate explanation to different niche breadth in sympatricFicedulaflycatchers

Abstract: Variation in relative fitness of competing recently formed species across heterogeneous environments promotes coexistence. However, the physiological traits mediating such variation in relative fitness have rarely been identified. Resting metabolic rate (RMR) is tightly associated with life history strategies, thermoregulation, diet use, and inhabited latitude and could therefore moderate differences in fitness responses to fluctuations in local environments, particularly when species have adapted to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 65 publications
2
15
1
Order By: Relevance
“…This is not surprising given the larger starting population as well as the fact that the pied flycatcher population on Öland is not isolated to the same extent as the collared flycatcher population and hints at selection rather than demography leading to these patterns. This relatively higher diversity is consistent with the observed adaptive plasticity in pied flycatcher RMR and could be the result of a better adaption to the variable northern climate (McFarlane et al 2018). We interpret the marked divergence in OXPHOS-related genes (including fixation of different non-synonymous mutations in mtDNA) together with signs of positive selection in both mitochondrial and nuclear genes encoding OXPHOS proteins for complex I and III as a legacy of different climate adaptation from the recent time in allopatry (Qvarnström et al 2016).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is not surprising given the larger starting population as well as the fact that the pied flycatcher population on Öland is not isolated to the same extent as the collared flycatcher population and hints at selection rather than demography leading to these patterns. This relatively higher diversity is consistent with the observed adaptive plasticity in pied flycatcher RMR and could be the result of a better adaption to the variable northern climate (McFarlane et al 2018). We interpret the marked divergence in OXPHOS-related genes (including fixation of different non-synonymous mutations in mtDNA) together with signs of positive selection in both mitochondrial and nuclear genes encoding OXPHOS proteins for complex I and III as a legacy of different climate adaptation from the recent time in allopatry (Qvarnström et al 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Collared and pied flycatchers diverged less than 1 million years ago (Nadachowska-Brzyska et al 2013) with strong postzygotic reproductive isolation in the form of hybrid dysfunction and infertility (Ålund et al 2013, McFarlane et al 2016, Svedin et al 2008). Here, we specifically focus on divergence in mtDNA and the interacting nuclear OXPHOS genes, as we have recently demonstrated that phenotypic differences in metabolic rate play important roles related to both differences in niche breath of the two species (McFarlane et al 2018) and hybrid dysfunction (McFarlane et al 2016). Using data from free-living collared, pied and hybrid flycatchers, we demonstrate distinct divergence in both the mtDNA (Figure 2) and in OXPHOS-related nDNA (Figure 3) of these species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, young pied flycatchers are often displaced from the preferred deciduous forests to mixed- and coniferous forest territories by collared flycatchers (Lundberg and Alatalo 1992 ; Qvarnstörm et al 2009 ; Veen et al 2010 ; Vallin et al 2012a , b ). Pied flycatcher nestlings also are better able to adjust their metabolism according to environmental changes (McFarlane et al 2018 ), which may partially explain their higher tolerance to low food availability. As incubation behaviour and thus the thermal environment during embryo development influences several physiological and developmental features of the off-spring, both in the short and longer term, it may thus also partly influence specie’s competitive ability and capacity to adapt to environmental changes.…”
Section: Introductionmentioning
confidence: 99%